BIFLAVONOID COMPOUND FROM THE STEM BARK OF GAMBOGE (Garcinia xanthochymus) - Muharni Muharni; Elfita Elfita; Amanda Amanda (Universitas Gadjah Mada, 2011)
Garcinia xanthochymus (Guttiferae) commonly known as gamboge, is a perennial medicinal plant native to the north of Thailand and Myanmar. Gamboge is used in watercolors, as a yellow fabric dye and traditional medicine for treating diarrhea and dysentery, dispelling worms clearing away fire and removing food toxin. Phytochemical investigations on the methanol extract of the stem bark of Garcinia xanthochymus resulted in isolation of one biflavonoid compound (+)-morelloflavon. The structure of this compound was deduced on basis of spectroscopic data including 1H NMR, 13C NMR, HMQC and HMBC and comparison with the reported data. This compound has been reported from others species of Garcinia.